(untitled) (World Economics and Finance Bulletin, 2022)
The enterprises of the real sector of the economy are one of the main sources and consumers of innovations. In this article, the author conducts an actual study of the mechanisms for stimulating the innovative activity of industrial enterprises. The role of innovations in ensuring economic growth is revealed. The tendencies in the change of innovative activity of the industry are investigated